2020
DOI: 10.21203/rs.3.rs-47847/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-Term HbA1c Variability and Cardiovascular Death: Insights from the EMPA-REG OUTCOME Trial

Abstract: Background: Glucose variability has been associated with cardiovascular (CV) outcomes in type 2 diabetes, however, the interplay between glucose variability, empagliflozin and CV death has not been explored. In the EMPA-REG OUTCOME trial, empagliflozin reduced the risk of CV death by 38%. We explore post-hoc the association between HbA1c variability and CV death, and the potential mediating effects of HbA1c variability on empagliflozin’s CV death reductions.Methods: In total, 7,020 patients with type 2 diabete… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…prospective cohort studies in the Asia Paci c region indicated that the FPG levels was a critical risk factor for cardiovascular disease, and that there were signi cant potential bene ts to reducing fasting glucose levels to at least 4.9 mmol/l in participants with/without diabetes [23] Additionally, reducing glycemic variability is an emerging glycemic target, and has been suggested as a critical predictor of cardiovascular complications. Several observational studies [7] and post-hoc analysis of trials, including the Action in Diabetes and Vascular Disease: Preterax and Diamicron MR Controlled Evaluation (ADVANCE) trial [9], the Veterans Affairs Diabetes Trial (VADT) [24], the Trial Comparing Cardiovascular Safety of Insulin Degludec vs. Insulin Glargine in Patients with Type 2 Diabetes at High Risk of Cardiovascular Events (DEVOTE) [25], the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial [26], and the Empagli ozin Cardiovascular Outcome Event (EMPA-REG OUTCOME) trial [27] demonstrated a positive association between visit-to-visit glycemic variability and the risk of micro/macrovascular disease in participants with type 2 diabetes. Furthermore, long-term glycemic variability has also been suggested to affect cardiovascular disease and mortality even in individuals without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…prospective cohort studies in the Asia Paci c region indicated that the FPG levels was a critical risk factor for cardiovascular disease, and that there were signi cant potential bene ts to reducing fasting glucose levels to at least 4.9 mmol/l in participants with/without diabetes [23] Additionally, reducing glycemic variability is an emerging glycemic target, and has been suggested as a critical predictor of cardiovascular complications. Several observational studies [7] and post-hoc analysis of trials, including the Action in Diabetes and Vascular Disease: Preterax and Diamicron MR Controlled Evaluation (ADVANCE) trial [9], the Veterans Affairs Diabetes Trial (VADT) [24], the Trial Comparing Cardiovascular Safety of Insulin Degludec vs. Insulin Glargine in Patients with Type 2 Diabetes at High Risk of Cardiovascular Events (DEVOTE) [25], the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial [26], and the Empagli ozin Cardiovascular Outcome Event (EMPA-REG OUTCOME) trial [27] demonstrated a positive association between visit-to-visit glycemic variability and the risk of micro/macrovascular disease in participants with type 2 diabetes. Furthermore, long-term glycemic variability has also been suggested to affect cardiovascular disease and mortality even in individuals without diabetes.…”
Section: Discussionmentioning
confidence: 99%